Cerebellar alterations in a model of Down syndrome: The role of the Dyrk1A gene - Susana García-Cerro; Verónica Vidal; Sara Lantigua; Maria Teresa Berciano; Miguel Lafarga; Pedro Ramos-Cabrer; Daniel Padro; Noemí Rueda; Carmen Martínez-Cué (Neurobiology of Disease, 2018)
Down syndrome (DS) is characterized by a marked reduction in the size of the brain and cerebellum. These changes play an important role in the motor alterations and cognitive disabilities observed in this condition. The Ts65Dn (TS) mouse, the most commonly used model of DS, reflects many DS phenotypes, including alterations in cerebellar morphology. One of the genes that is overexpressed in both individuals with DS and TS mice is DYRK1A/Dyrk1A (dual-specificity tyrosine-(Y)-phosphorylation regulated kinase 1A), which has been implicated in the altered cerebellar structural and functional phenotypes observed in both populations. The aim of this study was to evaluate the effect of Dyrk1A on different alterations observed in the cerebellum of TS animals. TS mice were crossed with Dyrk1A +/− KO mice to obtain mice with a triplicate segment of Mmu16 that included Dyrk1A (TS +/+/+), mice with triplicate copies of the same genes that carried only two copies of Dyrk1A (TS +/+/−), euploid mice that expressed a normal dose of Dyrk1A (CO +/+) and CO animals with a single copy of Dyrk1A (CO +/−). Male mice were used for all experiments. The normalization of the Dyrk1A gene dosage did not rescue the reduced cerebellar volume. However, it increased the size of the granular and molecular layers, the densities of granular and Purkinje cells, and dendritic arborization. Furthermore, it improved the excitatory/inhibitory balance and walking pattern of TS +/+/− mice. These results support the hypothesis that Dyrk1A is involved in some of the structural and functional cerebellar phenotypes observed in the TS mouse model.